SEXUAL VIOLENCE CASE PROFILE AT THE REGIONAL RSUD DR. RM. DJOELHAM BINJAI IN 2022 - Julanda, Baari Putra; Lubis, Adriansyah; Marbun, Doaris; Ismurizal, Ismurizal; Arviandi, Rizki (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Introduction Sexual crimes are crimes of morality in which every act committed by a person against another person results in sexual satisfaction for himself and disturbs the honor of others. In Indonesia, women and minors are often the victims of sexual crimes. Method This research is descriptive research with a cross-sectional approach. The population in this study was all data examined at the Forensic and Medicolegal Installation at Dr. RSUD. RM. Djoelham Binjai in 2022. The research sample was obtained from all data examined at the Forensic and Medicolegal Installation at RSUD Dr. RM. Djoelham Binjai on Sexual Violence Cases in Binjai City in 2022 using the total sampling method. Data collection was carried out using secondary data. Results Sexual violence cases examined in Dr. Hospital RM. Djoelham Binjai in 2022 were 46 victims. The highest number of cases of sexual violence based on age was in the early teens age group 12 - 16 years with 28 victims with a percentage of 60.8%. The number of women who experienced cases of sexual violence based on the relationship between the victim and the perpetrator, the highest was 42 victims who were people the victim knew with a percentage of 91.3%. The number of sexual violence cases based on the type of sexual violence was highest in cases of sexual abuse, 36 victims with a percentage of 78.3% and the lowest in rape cases, 10 victims with a percentage of 21.7%.